Kondisi Hati Dalam Al-Qur’an - Ahmad Haromaini (STAI Asy-Syukriyyah, 2017)
The potential of human dimili makes it able to carry out the mandate of Allah swt. as the Caliph on earth. The potential given of hearing, sight and heart (mind) became the main capital he was able to perform his duties of the Caliphate. The potential that is very important for humans is the heart that exists and has been buried by God Almighty. for him. As time passes and the tempo of life that has been experienced and has been witnessed, the hearts of human beings experience the ever-changing conditions. In themselves there is a surviving heart (saheeh) for being immersed by the faith and the virtues it has published, as well as the condition of the dead heart due to the sin which he has committed and the sick heart because of the acts of sin committed by the one who have confidence but still accompanied the sinful acts committed.